Utilization of Life Skills Training Results In Enhancing Self-Employed Alumni LKP Nuning Kota Cimahi - NISMA NURUL BILAD (IKIP Siliwangi Bandung, 2018)
Entrepreneurship is the right choice to improve the life of the economy independently. Whether it's the economy of ourselves personally, even the economy in general in a bigger scope. Cimahi City as one of the cities in Indonesia that has the number of unemployed as many as 2,903 people in 2015. Based on data obtained from the Department of Manpower Cimahi City in 2016, it is known that only about 25.2% alone the amount of unemployment that can be absorbed on the job there is. Based on the conditions in this field, needed an empowerment to overcome the condition. One of the empowerment activities that can be done to overcome this condition through life skills training in the field of bridal makeup organized by Course and Training Institute. But the activity of the alumni of post life skill training training needs to be seen again. Like what the alumni are applying the results of training in entrepreneurship. This research uses qualitative approach with descriptive method. The subject of this research is alumni of LKP Nuning Kota Cimahi in bridal make up. Data collection techniques in this study using interview techniques, observation, and documentation studies. The results of this study indicate that the life skills training process in bridal makeup field consists of preparation process, implementation process, evaluation process, and mentoring process. It can be said that 75% of LKP Nuning alumni in the field of bridal makeup have successfully entrepreneurship independently. This bridal makeup training really helps the alumni in improving their economic and social position in the community. After the training, the alumni began to pioneer their business independently. Promoting online and offline, improving existence through professional organization activities, as well as setting aside funds for upgrading on her dressing skills. In addition, they begin to encounter the obstacles in it. In general, the obstacles faced are divided into 4 issues namely, capital constraints, business competition obstacles, barriers to trend changes that are too fast, and hambantan management of business management. However, not all alumni succeeded in becoming bridal cosmetic. There are also alumni who return to their original job or remain a housewife. Keywords: Entrepreneurship Independence, Life Skills, Bridal Makeup